2013
DOI: 10.1055/s-0033-1350615
|View full text |Cite
|
Sign up to set email alerts
|

Success Rate of Inseminations Dependent on Maternal Age? An Analysis of 4246 Insemination Cycles

Abstract: !Intrauterine insemination (IUI) has latterly become less important in reproductive medicine. The aim of this retrospective analysis was to identify and evaluate the success rates of repeated insemination cycles in women of different ages. All women who underwent intrauterine insemination in the Wiesbaden Fertility Clinic between 1998 and 2010 were included in the analysis. Additional inclusion criteria were: not more than 45 years old, previous FSH stimulation and slight to moderate subfertility of the male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…A Dutch study, with a cohort of 946 couples, found that 51% had a live birth and that 28% had a naturally conceived pregnancy (Donckers et al, 2011). Cumulated pregnancy rates of 25-30% after four IUIcycles, in women under 35, are previously reported in two smaller, single center studies from Korea and Germany (Jeon et al, 2013;Schorsch et al, 2013). A randomized trial from the Netherlands compared birthrates after a maximum of six fresh cycles of IVF or six cycles of IUI in couples with idiopathic or male subfertility (Goverde et al, 2000).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A Dutch study, with a cohort of 946 couples, found that 51% had a live birth and that 28% had a naturally conceived pregnancy (Donckers et al, 2011). Cumulated pregnancy rates of 25-30% after four IUIcycles, in women under 35, are previously reported in two smaller, single center studies from Korea and Germany (Jeon et al, 2013;Schorsch et al, 2013). A randomized trial from the Netherlands compared birthrates after a maximum of six fresh cycles of IVF or six cycles of IUI in couples with idiopathic or male subfertility (Goverde et al, 2000).…”
Section: Discussionmentioning
confidence: 86%
“…dk). IUI is a well-tolerated and inexpensive alternative to ART, but it is also known to be less efficient per treatment cycle (Goverde et al, 2000;Steures et al, 2007;Jeon et al, 2013;Schorsch et al, 2013). Only a few smaller studies have investigated the long-term prognosis for live birth after ART and IUI (Sundström et al, 1997;Pinborg et al, 2009;Donckers et al, 2011;Aanesen and Westerbotn, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study was performed for the primary or secondary infertility patients who planned to undergo timed intercourse or intrauterine insemination at the Department of Assisted Reproduction of the Ninth People's Hospital of Shanghai Jiaotong University School of Medicine, as a result of failure to achieve pregnancy for at least one year without any birth control between December 2013 and June 2014. Patients eligible for participation in the study had to meet the following criteria: The women had regular menstrual cycles with normal ovulation and their husbands' total sperm count was at least 10 million/mL with a motility of at least 35% . Those women who had any systemic disease, active pelvic infection, follicle‐stimulating hormone greater than 15 IU/L, number of follicles fewer than 5, severe endometriosis (stage III and IV), or their husbands had asthenospermia and oligospermia were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…Patients eligible for participation in the study had to meet the following criteria: The women had regular menstrual cycles with normal ovulation and their husbands' total sperm count was at least 10 million/mL with a motility of at least 35%. 18 Those women who had any systemic disease, active pelvic infection, follicle-stimulating hormone greater than 15 IU/L, number of follicles fewer than 5, severe endometriosis (stage III and IV), or their husbands had asthenospermia and oligospermia were excluded from this study. All women were scheduled to receive 3D HyCoSy with normal saline injected into the pelvic cavity for the assessment of the patency of fallopian tubes and adhesions of the fimbriae.…”
Section: Methodsmentioning
confidence: 99%
“…Most patients are offered in vivo or in vitro treatment plans, and typically after implementation different procedures are selected based on the couple's diagnosis and previous treatment. In vivo fertilization cycles have a 5% to 15% success rate depending on the age of the woman (Schorsch et al, 2013). In the United States, the success rate or live birth rate for couples undergoing IVF is approximately 29% (CDC, 2015).…”
Section: Treatment Optionsmentioning
confidence: 99%